Exploring the Potential of Icelandic Seaweeds Extracts Produced by Aqueous Pulsed Electric Fields-Assisted Extraction for Cosmetic Applications - Natalia Castejón; Kristin Anna Thorarinsdottir; Ragnhildur Einarsdóttir; Kristberg Kristbergsson; Gudrún Marteinsdóttir (Marine Drugs, 2021)
A growing concern for overall health is driving a global market of natural ingredients not only in the food industry but also in the cosmetic field. In this study, a screening on potential cosmetic applications of aqueous extracts from three Icelandic seaweeds produced by pulsed electric fields (PEF) was performed. Produced extracts by PEF from Ulva lactuca, Alaria esculenta and Palmaria palmata were compared with the traditional hot water extraction in terms of polyphenol, flavonoid and carbohydrate content. Moreover, antioxidant properties and enzymatic inhibitory activities were evaluated by using in vitro assays. PEF exhibited similar results to the traditional method, showing several advantages such as its non-thermal nature and shorter extraction time. Amongst the three Icelandic species, Alaria esculenta showed the highest content of phenolic (mean value 8869.7 µg GAE/g dw) and flavonoid (mean value 12,098.7 µg QE/g dw) compounds, also exhibiting the highest antioxidant capacities. Moreover, Alaria esculenta extracts exhibited excellent anti-enzymatic activities (76.9, 72.8, 93.0 and 100% for collagenase, elastase, tyrosinase and hyaluronidase, respectively) for their use in skin whitening and anti-aging products. Thus, our preliminary study suggests that Icelandic Alaria esculenta-based extracts produced by PEF could be used as potential ingredients for natural cosmetic and cosmeceutical formulations.